Crohn's and Colitis Canada's 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: Executive Summary. (5th November 2021) - Ellen Kuenzig, M; Windsor, Joseph W; Barrett, Lisa; Bernstein, Charles N; Bitton, Alain; Carroll, Matthew W; Chauhan, Usha; Coward, Stephanie; Fowler, Sharyle; Ghia, Jean-Eric; Geist, Rose; Gibson, Deanna L; et al.
Abstract: Persons with inflammatory bowel disease (IBD) make up more than 0.75% of the Canadian population in 2021. Early in the COVID-19 pandemic, individuals with IBD, particularly those on immunosuppressive therapies, were concerned that their health status may place them at higher risk of contracting COVID-19 or experiencing more severe disease course if infected with SARS-CoV-2. In response, Crohn's and Colitis Canada developed the COVID-19 and IBD Taskforce in March 2020 to rapidly synthesize the evolving knowledge of COVID-19 as relevant to Canadians with IBD. The Taskforce communicated expert information directly to the Canadian IBD community through online tools and a webinar series. In order to understand the full impact of COVID-19 on the IBD community, Crohn's and Colitis Canada commissioned a policy report that was informed through a systematic literature review and synthesized across working groups along the following domains: Epidemiology, Children and Expectant Mothers with IBD, Seniors with IBD, Mental Health, Risk Factors and Medications, Vaccines, and Healthcare Delivery during the Pandemic and the Future Model of IBD Care. This report from Canadian physicians, researchers, and IBD community representatives highlights the physical, mental, and health systems impact of COVID-19 on the entire spectrum of the IBD community, including children, adolescents, adults, seniors, and pregnant people with IBD. This executive summary provides an overview of the crucial information from each of the chapters of the policy report, supplemented with additional information made available through Crohn's and Colitis Canada's webinar-based knowledge translation platform.